2015
DOI: 10.1063/1.4919135
|View full text |Cite
|
Sign up to set email alerts
|

On the structural origins of ferroelectricity in HfO2 thin films

Abstract: Here, we present a structural study on the origin of ferroelectricity in Gd doped HfO2 thin films. We apply aberration corrected high-angle annular dark-field scanning transmission electron microscopy to directly determine the underlying lattice type using projected atom positions and measured lattice parameters. Furthermore, we apply nanoscale electron diffraction methods to visualize the crystal symmetry elements. Combined, the experimental results provide unambiguous evidence for the existence of a non-cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
346
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 532 publications
(381 citation statements)
references
References 28 publications
(39 reference statements)
17
346
1
2
Order By: Relevance
“…In a later theoretical work, Huan et al 18 proposed that two orthorhombic phases with polar space groups of Pca2 1 and Pmn2 1 were possible to be the ferroelectric phases of HfO 2 , because their calculations showed that both Pca2 1 and Pmn2 1 phases had low free energies and small energy barriers for polarization switching. More recently, Sang et al 19 provided supportive evidence for the existence of the Pca2 1 phase as the structural origin of ferroelectricity in Gd:HfO 2 thin films using high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) in combination with position averaged convergent beam electron diffraction (PACBED (Figs. 2(a) and 2(b)).…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
“…In a later theoretical work, Huan et al 18 proposed that two orthorhombic phases with polar space groups of Pca2 1 and Pmn2 1 were possible to be the ferroelectric phases of HfO 2 , because their calculations showed that both Pca2 1 and Pmn2 1 phases had low free energies and small energy barriers for polarization switching. More recently, Sang et al 19 provided supportive evidence for the existence of the Pca2 1 phase as the structural origin of ferroelectricity in Gd:HfO 2 thin films using high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) in combination with position averaged convergent beam electron diffraction (PACBED (Figs. 2(a) and 2(b)).…”
Section: Origins Of Ferroelectricity In Hfo 2 -Based Materialsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Ferroelectric phenomenon in these doped-HfO 2 films deposited by various deposition techniques such as atomic layer deposition, [5][6][7][8][9][10] chemical solution deposition, 11 and sputtering 12 was mainly explained by the existence of noncentrosymmetric orthorhombic phase (space group of Pca2 1 ). 5,6,12 The dopant incorporation into monoclinic HfO 2 matrix results in a transformation to tetragonal/cubic phase with the appearance of an intermediate metastable orthorhombic (Pca2 1 ) phase.…”
mentioning
confidence: 99%
“…This discovery is of great interest to the semiconductor industry and has led to intensive experimental [3][4][5][6][7][8][9][10][11][12][13][14] and theoretical [9,[15][16][17][18][19][20][21][22] research, because these materials are believed to avoid the problems typical for the traditional ferroelectric materials (such as lead zirconate titanate) during integration into microelectronic devices. However, precise identification of the phase(s) in these films is problematic due to experimental limitations such as the broadness of the thin-film diffraction spectra, unknown film texture and strain fields, and possible presence of multiple phases within a single film.…”
mentioning
confidence: 99%
“…It is easy to see that this formulation of the "non-clashing" criterion actually implies that an entire "row" of atoms with given β, γ components (β, γ = α) has to have the sameα component of the displacement; thus, rather than enumerating the displacements of individual oxygen ions, only the displacements ofx,ŷ, andẑ rows of oxygen ions need be enumerated. 5 This reduces the number of the "non-clashing" "initial" configurations to the manageable ∼ 5.3 × 10 5 , starting from a cubic fluorite cell. We implemented our enumeration procedure as an atkpython script within Virtual NanoLab (VNL) [36].…”
mentioning
confidence: 99%
See 1 more Smart Citation